Implementation of the Adiwiyata Program Independent Proficiency Life Skills of Elementary School Students in Palu City - Muh Annas Abdillah; Samsurizal M. Suleman; I Made Budiarsa (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
School adiwiyata level independent is Schools that implement it behavior caring and cultured environment at school with 95% percentage , level participation participant educate in PBLHS movement already tall However based on studies introduction Still Lots students who haven't own knowledge environment and management good self .Study This aim For describe influence of the Adiwiyata program on personal skills, social skills, academic skills and vocational skills of Adiwiyata Elementary School students independent in Palu City. Study This is research descriptive with method study qualitative . Population in study This is all over Adiwiyata Elementary School students Palu City has a total of 693 students whereas amount samples in research This is 247 students . The instruments used _ is student life skills questionnaire consisting of of 32 statements . Results obtained is a student's personal skill are in the category good , students' social skills is in the very good category , student academic skills are in the category good and vocational skills of students is in the very good category .